2006
DOI: 10.1186/1745-0179-2-17
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundInformation on mental health sequel in adolescents following natural disasters from developing countries is scant.MethodAround one year after a super-cyclone, proportion of adolescents exhibiting post-traumatic psychiatric symptoms, prevalence of post-traumatic stress disorder (PTSD), major depression and generalized anxiety disorder, comorbidity and impairment of performance in school were studied in Orissa, India. Mini International Neuropsychiatric Interview for children and adolescents was used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(90 citation statements)
references
References 17 publications
5
84
0
1
Order By: Relevance
“…Studies show high comorbidity between depression and PTSD in a variety of population samples, such as those from conflict or post-conflict settings (Miller & Rasmussen, 2010), refugee camps (Gerritsen et al, 2006; Momartin, Silove, Manicavasagar, & Steel, 2004) and combat situations, victims of interpersonal violence (Stein & Kennedy, 2001), or survivors of natural or human-made disasters (Fernando, Miller, & Berger, 2010; Kar & Bastia, 2006; Neria, Nandi, & Galea, 2008). Political and economic instability and disparity; poverty, with its consequences of food scarcity and lack of access to medical care and education; politically motivated violence; crime; and exposure to weather phenomena due to climate change, which impacts negatively on an agriculture-based country such as Zimbabwe, further contribute towards poor mental health outcomes (Lund et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show high comorbidity between depression and PTSD in a variety of population samples, such as those from conflict or post-conflict settings (Miller & Rasmussen, 2010), refugee camps (Gerritsen et al, 2006; Momartin, Silove, Manicavasagar, & Steel, 2004) and combat situations, victims of interpersonal violence (Stein & Kennedy, 2001), or survivors of natural or human-made disasters (Fernando, Miller, & Berger, 2010; Kar & Bastia, 2006; Neria, Nandi, & Galea, 2008). Political and economic instability and disparity; poverty, with its consequences of food scarcity and lack of access to medical care and education; politically motivated violence; crime; and exposure to weather phenomena due to climate change, which impacts negatively on an agriculture-based country such as Zimbabwe, further contribute towards poor mental health outcomes (Lund et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have shown that stakeholders often underestimate both the intensity and duration of the stress reactions in children (5, 6). Acute stress reactions, adjustment disorder, depression, panic disorder, PTSD, anxiety disorders specific to childhood, and phobias are among mental health morbidities that have been commonly documented following disasters in children (7, 8). In a study of adolescent and youth among displaced Ethiopians, more than 90% of the sample lost their property, 70% suffered extreme thirst, and more than a third witnessed death (9).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents exposed to natural disasters are at high risk for posttraumatic stress disorder (PTSD; Garrison et al, 1995; La Greca, Silverman, Vernberg, & Prinstein, 1996), depression (Kar & Bastia, 2006; Warheit, Zimmerman, Khoury, Vega, & Gil, 1996), use of tobacco (Parslow & Jorm, 2006) and alcohol products (Reijneveld, Crone, Verhulst, & Verloove-Vanhorick, 2003; Rohrbach, Grana, Vernberg, Sussman, & Sun, 2009). The ability of organized care settings to render treatment to adolescents with such diagnoses is impaired after a natural disaster, however (Self-Brown, Anderson, Edwards, & McGill, 2013).…”
mentioning
confidence: 99%